Mean European Carbon Sink Over 2010–2015 Estimated by Simultaneous Assimilation of Atmospheric CO2, Soil Moisture, and Vegetation Optical Depth. Issue 23 (4th December 2019) - Scholze, M.; Kaminski, T.; Knorr, W.; Voßbeck, M.; Wu, M.; Ferrazzoli, P.; Kerr, Y.; Mialon, A.; Richaume, P.; Rodríguez-Fernández, N.; Vittucci, C.; Wigneron, J.‐P.; et al.
Abstract: The northern land biosphere is believed to be the main global sink of CO2, but the contribution of Europe is uncertain. While bottom‐up estimates and inverse atmospheric transport studies based on atmospheric CO2 observed in situ or from space by OCO‐2 point to a moderate rate of uptake, some other inversions based on remotely sensed atmospheric CO2 from GOSAT/SCIAMACHY and biomass estimates from passive microwave satellite data point to a large sink of around 1 Gt C/yr. We present results from combining both approaches in a data assimilation framework, inverting a biosphere model against in situ atmospheric CO2 and passive microwave measurements. When assimilating all observations, we estimate a European carbon sink of 0.303 ± 0.083 Gt C/yr for 2010–2015. The result agrees with other bottom‐up studies and atmospheric inversions using in situ CO2 or OCO‐2 observations pointing to potential data problems when using observations from GOSAT or SCIAMACHY to estimate the European CO2 sink. Key Points: European carbon sink estimated to be 0.303 ± 0.083 GtC/yr Consistent assimilation of three observational data products into a terrestrial biosphere model SMOS soil moisture and vegetation optical depth reduce flux uncertainty by an additional 15–25% compared to assimilating CO2 only